Unleashing the potential of local governments in pandemic response. Issue 6 (18th August 2021) - Yilmaz, Serdar; Boex, Jamie
ABSTRACT: All disasters are local with important repercussions for national and sometimes for international levels. An effective emergency response requires mobilising local government resources in the fight against disasters, including pandemics. Local governments, being closer to people, are well-positioned to identify local vulnerabilities and design appropriate response actions. This paper reviews relevant literature on the role of local government in the fight against pandemics and identifies two important prerequisites in deploying local governments effectively in fighting against pandemics: the existence of an intergovernmental coordination mechanism, and local government capacity. The research methodology includes a content analysis of qualitative and quantitative information through a literature review and available data in the public domain.